Hydrogen evolution reaction mechanism on pristine and defective nickel phosphate surfaces - Dyah Puspasari Wijayanti; Muhammad Arkan Nuruzzahran; Dzaki Ahmad Syaifullah; Damar Rastri Adhika; Hamad AlMohamadi; Nadhratun Naiim Mobarak; Ni Luh Wulan Septiani; Adhitya Gandaryus Saputro (Results in Surfaces and Interfaces)
We have investigated the hydrogen evolution reaction (HER) mechanism on various facets of nickel phosphate (NiPO) using density functional theory-based calculations. The results reveal that the (100) and (011) facets are the most stable surface facets due to their low surface energy. These facets exhibit weaker hydrogen adsorption energies at the oxygen sites, which enhances product desorption and leads to improved HER performance. Additionally, our findings successfully reproduce experimental trends observed for NiPO, platinum, and nickel catalysts. The data suggests that optimizing the surface structure, particularly by enriching the (100) facet with oxygen vacancies, could further enhance the HER performance of NiPO materials.